Hubungan Dukungan Keluarga dengan Tingkat Kecemasan Pasien Pre Operasi Sectio Caesarea di RSU Bhakti Asih Tangerang - Asha Grace Sicilia; Dessi Juwita; Indriani Febrishaummy Gunawan (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2025)
Sectio saesarea is a surgical procedure in which a baby is deliverd through an incision in the skin, abdominal muscles, and uterus. This procedure, along with its potential complications, can lead to anxiety in patients prior to delivery. This study aims to examine the relationship between family support and anxiety levels in pre- operative sectio caesarea patients at RSU Bhakti Asih Tangerang. The research employed a cross-sectional design with a quota sampling technique. The sample consisted of 66 patients meeting the inclusion and exclusion criteria. Data were collected using questionnaires that assessed family support and anxiety levels, measured with the Likert scale and the Zung Self-Rating Anxiety Scale, respectively. Data analysis was conducted using the Spearman Rho test with a total sample size of 66 participants. The results of the study revealed a significant negative correlation between the two variables. The Spearman correlation coefficient of -0.506 indicates a moderate negative correlation, with a significance level of 0.000 (p < 0.05). This finding demonstrates a significant relationship between family support and the anxiety levels of pre-operative patients. Therefore, healthcare professionals are encouraged to promote optimal family support for patients in pre-operative situations to achieve the best possible outcomes for the patients.